Hubungan Nilai Kemampuan Interpersonal dan Komunikasi dengan Nilai Bimbingan dan Konseling Mahasiswa PGSD - Hajar Nurul Izzati; Jesi Alexander Alim; Zakiah Ulya (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
The Interpersonal and Communication Skills course plays an important role in equipping elementary teacher education (PGSD) students with the ability to build positive relationships, understand others’ feelings, and communicate information effectively. These skills are believed to influence success in the Guidance and Counseling course, which requires students to understand socio-emotional dynamics and analyze problems based on theory. This study aims to determine the relationship between the final grades of the Interpersonal and Communication Skills course and the Guidance and Counseling course among PGSD students. This research employed a quantitative correlational approach. The sample consisted of 28 PGSD students from the University of Riau, class of 2023, group B, who had completed both courses in the fourth semester. Data were obtained from the final grades of both courses and analyzed using the Spearman Rank correlation test. The results showed a correlation coefficient of 0.146 with a Sig. (2-tailed) value of 0.458 (p > 0.05). These findings indicate that there is no significant relationship between the two variables. The results suggest that students’ academic achievement in the Guidance and Counseling course is more strongly influenced by theoretical mastery and analytical skills rather than differences in grades in the Interpersonal and Communication Skills course.